PENINGKATAN PRODUKTIVITAS PENGRAJIN EMPING MELINJO MELALUI IMPLEMENTASI TEKNOLOGI TEPAT GUNA - Romli, Ombi; Putra, Arta Rusidarma; Meilisa, Ranny (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
Emping melinjo is one of the crunchy savory snacks made from old melinjo seeds where the manufacturing process is very unique. Melinjo seeds are roasted first, then flaked to produce emping that is ready to be fried. However, the flaking process can be time-consuming and labor-intensive and risky for the craftsmen. Hand injuries due to hammer blows and non-erogonomic working positions can hinder the production process and reduce production yields, thus becoming an obstacle for the puff pastry crafters in Jaha Village, Sindang Mandi Village, Anyer, Serang Regency. The modern puff pastry flattener comes as a solution to improve the efficiency and safety of the production process. This tool can flatten melinjo quickly and precisely, without safety risks and more comfortable for craftsmen. The method carried out in four stages, namely planning which includes identifying problems in making melinjo chips, testing the tool, training partners on the use of the tool and evaluation. The results of this activity are that the emping craftsmen in Jaha Village, Sindang Mandi Village, Anyer, Serang Regency can continue to preserve the tradition of making melinjo chips and the emping craftsmen can work more safely, efficiently, and productively so as to produce higher quality melinjo chips